Tracing financial innovations diffusion and substitution trajectories. Recent evidence on exchange traded funds in Japan and South Korea - Adam Marszk; Ewa Lechman (Gdańsk University of Technology, Faculty of Management and Economics, 2016)
Similar to economic growth, the process of technology diffusion may well be approximated by easily Exchange Traded Funds (ETFs) are recognized financial innovations pervasively impacting and transforming financial markets (Deville 2008, Gastineau 2010, Agapova 2011, Hill et al. 2015). Easy to use they have gained rapidly growing popularity among investors (Gastineau 2010, Lechman and Marszk 2015). Asian countries are those where rapid spread of financial innovations is observed (Marszk 2014); hence our analysis covers Japan and South Korea, which allows comparing diffusion and substitution trajectories of innovative financial products between advanced and emerging economy. It also traces substitution effects between ETFs and index derivatives. Moreover, we claim that ETFs influence financial systems in various ways, and may impact their stability, due to e.g. liquidity risk (Kosev and Williams 2011, Foucher and Gray 2014), and this also constitutes a field of our research. Our research contributes to the present state of knowledge by:Tracing diffusion trajectories of financial innovations (ETFs) and examination of the dynamics of the process, across Japanese and South Korean stock exchanges;Examining the unique process of substitution between ETFs and similar investment options, i.e. stock index futures and options;Providing long-term predictions of financial innovations development across examined countries: trying to establish the possible future path of the ETF markets development in countries in scope;Examination of the impact of the ETFs on the financial systems in examined countries; identification of country-specific thresholds leading to emergence of possible threats for the financial system stability.
Keywords: G10; G15; 330; ETFs; financial innovations; financial substitution